(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Sport, which is considered an integral part of the physical culture of society, basically means "work", "compete". Until the end of the 19th and beginning of the 20th century, it was considered as a means of recreation, entertainment, and then as a means of achieving high physical performance and winning competitions.